Accountability in the post-Lisbon European Union1. (December 2016) - Jan Brandsma, Gijs; Heidbreder, Eva; Mastenbroek, Ellen
This special issue takes stock of recent post-Lisbon additions to the European Union's accountability toolkit. It provides indications that older decision-making tools tend to be more accountable than newer ones, and that, in some areas, decision-making is shifting towards less accountable arenas. This introductory article reviews the debate on the gradual evolution of the European Union's accountability system and introduces key aspects of the post-Lisbon era that can be expected to affect accountability in the European Union, and that have been overlooked by the literature thus far: delegated acts, economic governance and regulatory evaluations. The contributions to this special issue address each of these domains in detail and highlight the degree to which accountability has been enhanced. A final contribution shows how these arrangements fit into the wider landscape of already-existing European Union accountabilities and how this landscape has developed over time. Points for practitioners: There is an apparent link between the relative novelty of the institutional setting in which a governance system is embedded and its accountability. Settings that include a strong role for the European Commission tend to be the most accountable ones, while those that rely mostly on intergovernmental logics, including those that have been created outside the Treaty framework, come with significant gaps.